2020
DOI: 10.1007/s42421-020-00024-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Hard-Braking Activity with Crash Occurrences on Interstate Construction Projects in Indiana

Abstract: The Federal Highway Administration (FHWA) reported between 2016 and 2017, fatal crashes in work zones increased by 3%, while fatal crashes outside of work zones decreased by 1.5%. The FHWA also reported that work zones account for approximately 10% of the nation’s overall congestion and 24% of unexpected interstate delays. This paper reports on a study of 23 construction work zones that covered approximately 150 centerline miles of Indiana interstate roadway in the summer of 2019. Approximately 50% of all inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Every month, hundreds of billion passenger Journal of Transportation Technologies vehicle trajectory waypoints, consisting of latitude, longitude, heading, speed, and timestamp, are collected in the United States. The resulting data sets can provide agencies with a plethora of historically difficult to collect data, such as traffic signal performance measures, hard-braking events, interstate congestion, and common detours around road closures [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Every month, hundreds of billion passenger Journal of Transportation Technologies vehicle trajectory waypoints, consisting of latitude, longitude, heading, speed, and timestamp, are collected in the United States. The resulting data sets can provide agencies with a plethora of historically difficult to collect data, such as traffic signal performance measures, hard-braking events, interstate congestion, and common detours around road closures [1] [2] [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…A high R 2 value suggests the linear trendline is able to explain most of the dataset. Past studies have indicated a strong relationship between hard-braking and crashes [23]. This clear reduction in hard-braking events for queue warning trucks with alerts is anticipated to reduce crashes by a similar proportion.…”
Section: Longitudinal Analysis Of Queue Warning Truck Impactmentioning
confidence: 94%
“…But crashes are often reported with a time lag and underreported due to a variety of reasons [19] [20] [21], including the unwillingness of involved drivers to report a crash [22]. A study conducted on 23 construction work zones that covered approximately 150 centerline miles of Indiana interstate roadway in the summer of 2019, found that there was approximately 1 crash for every 147 hard-braking events in and around a construction site with an R 2 value of 0.85 [23]. Thus, the new commercially available hard-braking data sources provide an opportunity for agencies to follow up with mitigation measures addressing emerging problems much quicker than typical practices that rely on 3 -5 years of crash data [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heavy braking (HB) is used as an indication of rapid deceleration and to detect collisions or dangerous situations. Based on the literature review [41], a threshold value of −2.5 ms −2 was identified as applicable to the analysis in this study, meaning that values greater than −2.5 ms −2 were considered heavy braking, and were consequently considered to be potential conflicts. A total of six potential HB conflicts were identified.…”
Section: Heavy Brakingmentioning
confidence: 99%